Aboriginal families living with MJD in remote Australia: questions of access and equity - Libby Massey; John Gilroy; Emma Kowal; Denise Doolan; Alan Clough (BMC, 2024)
Abstract Managing genetic disease using medically assisted reproductive technology is increasingly promoted as a feasible option, given revolutionary advances in genomics. Far less attention has been directed to the issue of whether there is equitable access to this option. Context and circumstance determine equitable access; however, reporting has drawn overwhelmingly from affluent Anglo-western populations in developed countries. The experiences of poorer, less educated subpopulations within affluent countries and populations in less developed countries are underreported. The ability of consumers to understand the opportunities and risks of medically assisted reproductive technology is likewise not well described in the literature despite significant technological complexity and evidence that genetic disease may be overrepresented within some disadvantaged population groups. Equity is achieved by identifying barriers and allocating appropriate resources to enable understanding and access. In the case of utilising medically assisted technology, social and power relationships, regulations, and the presumptions of authority figures and policymakers reduce equitable access. Physical or cultural marginalisation from mainstream health services may result in reduced access to genetic and prenatal testing, in-vitro fertilisation and genetic screening of embryos necessary for medically assisted reproduction. Cost and regulatory frameworks can likewise limit opportunities to engage with services. Moreover, the quality of the information provided to prospective users of the technology and how it is received governs understanding of prevention and inhibits adequately informed choice. Best practice care and adequately informed choice can only be achieved by conscientiously attending to these accessibility issues. Deep engagement with at-risk people and critical reflection on mainstream accepted standpoints is required. This paper outlines issues associated with engaging with medically assisted reproduction encountered by Aboriginal families living with Machado-Joseph Disease in some of the most remote areas of Australia. It is the right of these families to access such technologies regardless of where they live. Current barriers to access raise important questions for service providers with implications for practice as new technologies increasingly become part of standard medical care.